2006
DOI: 10.1037/0003-066x.61.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary metrics in psychology.

Abstract: Many psychological tests have arbitrary metrics but are appropriate for testing psychological theories. Metric arbitrariness is a concern, however, when researchers wish to draw inferences about the true, absolute standing of a group or individual on the latent psychological dimension being measured. The authors illustrate this in the context of 2 case studies in which psychologists need to develop inventories with nonarbitrary metrics. One example comes from social psychology, where researchers have begun usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
471
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(481 citation statements)
references
References 36 publications
6
471
0
4
Order By: Relevance
“…On the startle-probe, however, the (same) smoking pictures significantly suppressed startle responses in comparison to neutral pictures and therefore acted in a similar fashion to positive pictures (Cuthbert et al, 1996). Put another way, on the IAT the smoking pictures appeared to receive an automatic negative evaluation (but see comments above on the IAT's zero point, Blanton and Jaccard, 2006), whereas on the startle-probe they appeared to receive an automatic positive evaluation. This might be explained if the societal influences noted above impact the IAT effect more than startle-probe responses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the startle-probe, however, the (same) smoking pictures significantly suppressed startle responses in comparison to neutral pictures and therefore acted in a similar fashion to positive pictures (Cuthbert et al, 1996). Put another way, on the IAT the smoking pictures appeared to receive an automatic negative evaluation (but see comments above on the IAT's zero point, Blanton and Jaccard, 2006), whereas on the startle-probe they appeared to receive an automatic positive evaluation. This might be explained if the societal influences noted above impact the IAT effect more than startle-probe responses.…”
Section: Discussionmentioning
confidence: 96%
“…A negative IAT effect has generally been interpreted in the literature as reflecting a negative implicit attitude to smoking (preference for smoking over not smoking). Blanton and Jaccard (2006) have argued that the location of the IAT's zero point has not yet been firmly established, and so the meaning of absolute IAT scores is uncertain. On the other hand, Greenwald et al, (2006) provided evidence that the observed zero point corresponds to the true zero point in one context (preference for one presidential candidate over another).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, even if racial attitudes are a direct cause of scores on a racial IAT, it is not certain that a zero score on the racial IAT means that the person likes Black and White individuals to the same extent. Because of this fact, the IAT effect shown by a particular individual can be interpreted only by comparing it with the IAT effects of other persons (e.g., Person A has more positive attitudes toward White persons or less positive attitudes toward Black persons than does Person B; but see Greenwald, Nosek, & Sriram, 2006, for a critique of Blanton & Jaccard, 2006).…”
Section: Iat Effects the What Criterion: What Attributes Cause Variatmentioning
confidence: 99%
“…Importantly, the IAT can only measure relative attitudes (e.g., attitudes to fat people relative to attitudes to thin people). It is therefore impossible to determine using the IAT whether this bias is the result of a strong/weak pro-thin bias, a strong/weak anti-fat bias or some combination of the two (see Blanton & Jaccard, 2006;Roddy, Stewart, & Barnes-Holmes, 2011;2012). Likewise, the IAT cannot be used to determine how interventions that aim to increase or reduce implicit biases have their effect (e.g., a difference in implicit attitudes could be reduced by acting on the 'Thin Person' category, the 'Fat Person' category, or both; see Lai et al, in press).…”
Section: Absolute Vs Relative Measures Of Implicit Cognitionmentioning
confidence: 99%